PENGARUH MEDIA TANAM COCOPEAT TERHADAP PERTUMBUHAN SEMAI AREN (Arenga pinnata Merr.) - Khoirunnisa Khoirunnisa; M Mardhiansyah; Mukhamadun Mukhamadun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Arenga pinnata is a commodity that has high economic value, but hasn’t been utilized optimally. The population of Arenga pinnata is decreasing. This happens because forest encroachment and felling of Arenga pinnatatrees are not balanced with the regeneration of young plants. Based on the nature ofArenga pinnataand its utilization, it is recommended to plant in stages so that the availability of plants is guaranteed.Cocopeat growing media is suitable for rehabilitation of critical land in dry climates. Cocopeat functions to keep plant roots from drying out and hydrated properly. The research was carried out using a Completely Randomized Design (CRD) consisting of 4 treatments with 5 replications in order to obtain 20 experimental units. Each replication consisting of 5 experimental samples, so that the total seedling used is 100 experimental units. This research used 4 treatments with cocopeat composition, P1 = 100% soil planting medium as control P2 = 75% soil planting medium + 25% cocopeat P3 = 50% soil planting medium + 50% cocopeat P4 = 25% soil planting medium + 75 cocopeat %. The data obtained from the results of the study were statistically analyzed using Analysis of Variance (ANOVA) and using Duncan's New Multiple Range Test (DNMRT) at the 5% level. Cocopeat growing media has a significant effect on leaf surface area. The composition of the best cocopeat growing media used for the growth of Arenga pinnata seedlings is a composition of 75% cocopeat + 25% soil, with 100% percentage live of seedlings, an increase in seedling height of 10,08 cm, leaf surface area of 102 cm2.Keywords: Arenga pinnata, cocopeat, growth